Criminal Responsibility in Documents Forgery of Applying Credit Card - Silvia Anggraini; Y. A Triana Ohowaitun; Ainul Azizah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
This research discusses criminal liability in cases of forgery of documents in credit card applications which contain an element of inclusion. Forgery of documents in Articles 263 to 276 of the Criminal Code. This research uses a normative juridical research method using three approaches, namely the statutory approach, conceptual approach, and case approach. Consisting of two problem formulations, namely 1) What is the article alleged by the Public Prosecutor in Decision no. 357/Pid.B/2019/PN.Jkt.Pst and Decision No. 358/Pid.B/2019/PN.Jkt.Pst are in accordance with the acts of participation carried out by the defendant? 2) What is the judge's consideration in handing down a decision against the perpetrator of the crime of document forgery in Decision No. 357/Pid.B/2019/PN.Jkt.Pst and Decision No. 358/Pid.B/2019/PN.Jkt.Pst are in accordance with the defendant's guilt? This research results that 1) the element of inclusion in the indictment made by the public prosecutor is not clear about the direction of participation, because the articles being targeted are different, so the indictment must be statedobsciuur libel. 2) the judge's considerations in handing down a decision regarding the criminal act of forgery of documents in decision no. 357/Pid.B/2019/PN.Jkt.Pst is in accordance with the defendant's error, namely fulfilling the element of error by intentionally falsifying a letter, and decision no. 358/Pid.B/2019/PN.Jkt.Pst has fulfilled the element of error by deliberately using a fake letter. However, because one of the elements of the indictment, namely the inclusion element, is considered unclear, one of the decisions must be null and void.